Development of student worksheets based on the PBL model to improve students' critical thinking ability - Dewi Nurhasanah Nasution; Reh Bungana Boru Perangin-angin; Wildansyah Lubis (Inovasi Kurikulum, 2026)
In the 21st century, students need to possess 4C skills: critical thinking, collaboration, communication, and creativity. In improving students' critical thinking skills through the learning process, it is highly dependent on learning resources, for example Student Worksheets (LKPD). This study aims to develop and determine the feasibility, practicality, and effectiveness of Problem Based Learning (PBL)-based LKPD developed for the critical thinking skills of fourth-grade students of SD Negeri 101775 Sampali. This study is a Research and Development (RnD) study using the ADDIE model approach, namely Analysis, Design, Development, Implementation, and Evaluation. The research instruments used are observation, questionnaires and critical thinking ability tests. The results of the study indicate that PBL-based LKPD is suitable for use, based on the feasibility test of LKPD products by the validator. Based on teacher and student responses, PBL-based LKPD is very practical to use with the results of responses obtained by two teachers and the results of student responses. PBL-based LKPD is effective to use with the criteria of "Medium". It can be concluded that the PBL-based LKPD developed is feasible, practical, and effective in improving students' critical thinking skills.   Abstrak Pada abad 21, peserta didik perlu memliki keterampilan 4C yakni berpikir kritis, kolaborasi, komunikasi, dan berpikir kreatif. Dalam meningkatkan kemampuan berpikir kritis peserta didik melalui proses pembelajaran sangat bergantung pada sumber pembelajaran, misalnya Lembar Kerja Peserta Didik (LKPD). Penelitian ini bertujuan untuk mengembangkan dan mengetahui kelayakan, kepraktisan, serta keefektifan LKPD berbasis Problem Based Learning (PBL) yang dikembangkan terhadap kemampuan berpikir kritis peserta didik kelas IV SD Negeri 101775 Sampali. Penelitian ini merupakan penelitian Research and Development (RnD) dengan menggunakan pendekatan model ADDIE yaitu Analysis, Design, Development, Implementation, and Evaluation. Instrumen penelitian yang digunakan yaitu observasi, angket dan tes kemampuan berpikir kritis. Hasil penelitian menunjukkan bahwa LKPD berbasis PBL sudah layak digunakan, berdasarkan uji kelayakan produk LKPD oleh validator. Berdasarkan respons guru dan peserta didik LKPD berbasis PBL sangat praktis digunakan dengan perolehan hasil respons oleh dua orang guru dan hasil respons peserta didik. LKPD berbasis PBL efektif digunakan dengan kriteria “Sedang”. Dapat disimpulkan bahwa LKPD berbasis PBL yang telah dikembangkan layak, praktis, dan efektif untuk meningkatkan keterampilan berpikir kritis peserta didik. Kata Kunci: berpkir kritis; lembar kerja peserta didik; LKPD; PBL; pembelajaran berbasis masalah